2015
DOI: 10.1186/s13045-015-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-based therapeutic intervention of cancer

Abstract: MicroRNAs (miRNAs) are important modulators of eukaryotic gene expression. By targeting protein coding transcripts, miRNAs influence the cellular transcriptome and proteome, thus helping to determine cell fate. MiRNAs have emerged as crucial molecules in cancer research, in which recent studies have linked erratic expression of miRNAs to carcinogenesis and have provided solid evidence for their potential in cancer therapy. This review briefly summarises the recent knowledge on the involvement of miRNAs in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 113 publications
(73 reference statements)
0
74
0
Order By: Relevance
“…m iR NAs a re deregulated in numerous human cancers (23,24). Previous studies have demonstrated that miRNAs are reliable and cost-effective biomarkers that can be utilized in the diagnosis and assessment of the progression, therapeutic response and prognosis of a wide spectrum of malignant tumors, including esophageal cancer (7,(25)(26)(27). A better understanding of the miRNAs associated with particular cancers would provide valuable insights for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…m iR NAs a re deregulated in numerous human cancers (23,24). Previous studies have demonstrated that miRNAs are reliable and cost-effective biomarkers that can be utilized in the diagnosis and assessment of the progression, therapeutic response and prognosis of a wide spectrum of malignant tumors, including esophageal cancer (7,(25)(26)(27). A better understanding of the miRNAs associated with particular cancers would provide valuable insights for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified an association between dysregulated miRNA expression and cancer diagnosis (28,29). In addition, it has been demonstrated that miRNAs modulate numerous signaling pathways and regulate the expression of thousands of genes (7,30). The current gold standard of cancer diagnosis is a pathological diagnosis, due to the heterogeneous nature of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have suggested that miRNAs perform a crucial role in regulating cancer cells by acting as oncogenes or tumor suppressers (9)(10)(11). Therefore, miRNAs may serve as potential biomarkers and targets for the diagnosis and treatment of various types of cancer (12). miRNA-34a is an important regulator of tumor suppression, and acts by controlling cellular proliferation, cellular differentiation and the survival of cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…Several miRs have been reported to have an important role in tumor metastasis (45)(46)(47). Furthermore, since miRs regulate multiple target genes simultaneously, miR-based therapy is expected to be more efficient than the traditional single target therapy (48,49). In the present study, miR-429 was shown to be an important regulator in tumor cell migration and invasion, which emphasized an essential role of miR-429 in regulating GC metastasis.…”
Section: Discussionmentioning
confidence: 53%